2021
DOI: 10.1029/2021gc009686
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Late Cenozoic Magmatism in the South China Sea and Southeast Asia

Abstract: Basaltic lavas sample recycled crustal materials from their mantle source. Constraining the location and residence time of these recycled materials in the mantle is critical to understand global mantle dynamics. In this study, we present new whole‐rock major and trace element abundances, Sr‐Nd‐Mo‐Os isotopes, water contents and He isotopes of volcanic glasses, U‐Pb ages of zircons, and compositions of melt inclusions, spinels and olivines from the South China Sea (SCS) seamounts lavas. These new data are compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 156 publications
(382 reference statements)
0
13
0
Order By: Relevance
“…The earlier studies for the basalts in Central Vietnam (An et al, 2017;Hoang et al, 2018) and the other volcanic fields adjacent to Central Vietnam (SE China and EVS/SCS; Y.-Q. Li et al [2020]; Qian et al [2021]) also estimated a similar composition for this component.…”
Section: Isotopic Characteristics Of Magma Sourcesmentioning
confidence: 57%
See 4 more Smart Citations
“…The earlier studies for the basalts in Central Vietnam (An et al, 2017;Hoang et al, 2018) and the other volcanic fields adjacent to Central Vietnam (SE China and EVS/SCS; Y.-Q. Li et al [2020]; Qian et al [2021]) also estimated a similar composition for this component.…”
Section: Isotopic Characteristics Of Magma Sourcesmentioning
confidence: 57%
“…Another recent study (Qian et al, 2021) also found geochemical characteristics which support the insignificant role of a pyroxenite source for the basalts from EVS/SCS seamounts. The study reported that olivine phenocrysts in basalts from EVS/SCS seamounts have a Ni abundance lower than those in Vietnamese basalts, but comparable to those found in MORB, yet the basalts from these two regions share common trace-element and isotopic characteristics.…”
Section: Lithology Of Magma Sourcesmentioning
confidence: 70%
See 3 more Smart Citations